Implementasi Program Peningkatan Perilaku Pemilahan Sampah Rumah Tangga, Revitalisasi“Smart Waste Management”, Dan Konversi “Waste To Energy” Di Kota Bekasi - Ricky Febri Saputra; Rahmat Hidayat; Rudyk Nababan (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2021)
In dealing with waste management problems in Bekasi City, the Bekasi City Government has implemented waste management innovations by involving the community's role through the Program for Improvement of Household Waste Segregation Behavior, Revitalization of